2006
DOI: 10.1111/j.1469-0691.2006.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of pneumococcal antigen detection in pleural fluid samples by immunochromatographic assay for diagnosis of pneumococcal pneumonia

Abstract: This study investigated the utility of an immunochromatographic test (ICT) for the detection of Streptococcus pneumoniae antigens in pleural fluid. Antigen was detected in 15 of 19 (79%) patients with pneumococcal pneumonia. The ICT was always negative in patients with non-pneumococcal pneumonia, but was positive in three cases with a non-infectious aetiology. In patients with pneumonia for which no pathogen was identified, antigen was detected in one of 24 pleural fluids tested. The ICT can be a valuable tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 12 publications
0
21
0
1
Order By: Relevance
“…The test proved negative in 20 documented cases of empyema due to other bacteria and there were two false positives (95% specificity). Andreo et al [2] found a sensitivity and specificity of 79% and 93.6%, respectively, for the pneumococcal antigen immunochromatographic test in parapneumonic pleural effusions diagnosed by conventional microbiologic methods, but not by PCR, thus explaining the better specificity. Charkaluk et al [3] evaluated the efficacy of the test in 287 children with suggestive clinical signs, not only with pleural effusion, and detected a high sensitivity (100%), low specificity (55.9%), and 10.7% of false negatives in nasopharyngeal carriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The test proved negative in 20 documented cases of empyema due to other bacteria and there were two false positives (95% specificity). Andreo et al [2] found a sensitivity and specificity of 79% and 93.6%, respectively, for the pneumococcal antigen immunochromatographic test in parapneumonic pleural effusions diagnosed by conventional microbiologic methods, but not by PCR, thus explaining the better specificity. Charkaluk et al [3] evaluated the efficacy of the test in 287 children with suggestive clinical signs, not only with pleural effusion, and detected a high sensitivity (100%), low specificity (55.9%), and 10.7% of false negatives in nasopharyngeal carriers.…”
Section: Discussionmentioning
confidence: 99%
“…This test has been validated for urine and cerebrospinal fluid [3,10,11,15], and has recently been studied for pleural fluid [2,8,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteremic infections tend to have higher rates of positivity [50,52]. Promising results have been reported for testing of pleural fluid for the diagnosis of empyema [44,53]. Finally, ICT has been used for management decisions.…”
Section: Pneumococcal Urinary Antigen Testingmentioning
confidence: 99%
“…Unlike in the case of patients with pneumococcal pneumonia or bacteremia, failures with b-lactam drugs is well described for meningitis [65][66][67]; so this test could be used to identify subsets of patients with meningitis that are more likely to benefit from the addition of a glycopeptide such as vancomycin to the standard antibiotic regimen. It can also be used with reasonable accuracy on samples of pleural fluid [68,69 ] and bronchoalveolar lavage fluid [70].…”
Section: Binaxnow Streptococcus Pneumoniae Urinary Antigen Testmentioning
confidence: 99%